The (re)making of a city centre: Jan Gehl and the transformation of Melbourne CBD - Chitrakar, Rajjan; Herriotts, Rosalind; Hogg, Peter (Journal of Architecture and Urbanism, 2025)
Jan Gehl, an eminent Danish Architect and Urban Designer, has worked in more than forty cities around the world and contributed to revitalising their city centres. Although his work in Australia has drawn considerable attention in recent years, not much is known about his early and exemplary work on revitalising the city centre in Melbourne. This paper explores Gehl’s urban design work in Melbourne by examining his engagement with the City of Melbourne after being invited to lead the ‘Places for People’ initiative in 1993. Gehl’s main contributions during his collaboration with the council include developing the methodology for the Public Space Public Life surveys and co-authoring of the Places for People study reports. Gehl made several key recommendations in the reports that turned out to be instrumental in formulating urban design approaches to help transform the Melbourne CBD into a vibrant city centre. This transformation, which led to the revival of the public realm, is evident in several significant changes made to some major public spaces between 1994 and 2004 and beyond. This paper contributes to the urban design discipline by adding new knowledge of Gehl’s work in Melbourne and widening its recognition in Australia and internationally.